Participation University of Guayaquil in the Study of Onchocerciasis in Ecuador - Lazo Salazar, Ramón (Revista Universidad de Guayaquil, 2012)
Importantly, the University of Guayaquil has been involved in the history of the Ecuadorian Onchocerciasis since its inception in 1980. Dr. Ramon Lazo teaching of parasitology at the Faculty of Medical Sciences and 1 Vice President of the Latin American Federation of Parasitologists (FLAP), invited the Guatemalan parasitologist Dr. Francisco Aguilar to participate in the Latin American Congress of Clinical Pathology, at the Symposium “Parasitic disease of greater importance in the tropics”, with the theme of Onchocerciasis. Invitation was sent FLAP directory: Dr. Rubens Campos (Brazil) as Chairperson; Dr. Francisco Aguilar (Guatemala), 2 nd Vice President and Dr. Benjamin Cimerman (Brazil), 3 rd Vice President. Unaware that Dr. Francisco Aguilar had designated the issue of “Onchocerciasis in Latin America” to be presented at the congress of Onchocerciasis in Guatemala-Japan, organized in January 1981. In the Summary of his work only joined the existence of the first case of onchocerciasis in Ecuador, to receive personal communication from Dr. Lazo, that Dr. Luis Carvajal had identified the first case of Ecuador. With fieldwork conducted with the assistance of professors of the Faculty of Medical Sciences, was expanded research data, being incorporated in the Guatemala-Japan joint conference, which was reported in the Proceedings of this event in 1981. The participation of the University of Guayaquil was eloquent, informed on News Gazette and in the Newsletter of Vice President Academic 1986, whose stories are below.